What are the perspectives of two teachers and their sixth-class students in two different DEIS schools on a problem-solving learning opportunity in the area of fractions? - Sweeney, Ciara (Marino Institute of Education, 2024)
An analysis of the literature indicates how children from areas of low socioeconomic status (SES) are more likely to be excluded from mathematical classes, have poorer learning opportunities, and have lower levels of self-efficacy (Jorgensen, 2016). In Ireland, the DEIS school system aims to support children in SES areas in a variety of ways to help increase their achievement levels across the curriculum including mathematics education. One area where pupils are deficient is problem solving (TIMMS, 2019). The revised Primary Mathematics Curriculum, which will be implemented in the academic year 2024–2025, aims to support students’ problem solving by making problems more engaging and relevant to real life. The research focuses on developing a learning opportunity in fraction problem solving for 6th class pupils in DEIS schools, which aligns with the new curriculum. A case study methodology was adopted, a two lesson learning opportunity was developed and delivered by teachers in two DEIS schools. Pre and post lesson implementation interviews with teachers were conducted, as well as learning surveys from pupils. Data was analysed thematically to address the research question. The findings reported the need for increased problem solving learning opportunities for pupils in DEIS schools in order to help consolidate learning and increase pupil self-efficacy. Furthermore, the findings highlighted the need for teacher training on how to effectively implement problem solving for pupils in primary school.
Keywords: Education; Primary school teachers; Qualitative research; Low socioeconomic status; DEIS Schools; Irish Primary Curriculum; Case Study; Problem-solving; Mathematics--Study and teaching; Education, Primary--Curricula